A method for producing coconut shell activated carbon fabric
By optimizing the processing technology of coconut shell carbon powder and the use of modified silicone and bisphenol A-type epoxy resin, the problems of limited antibacterial and deodorization properties and poor bonding strength of coconut shell activated carbon fabrics are solved, and efficient deodorization, antibacterial effects and good bonding properties are achieved.
Patent Information
- Application Number
- CN202510059083.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The antibacterial and deodorizing properties of existing coconut shell activated carbon fabrics are limited and have poor bonding strength.
By optimizing the processing technology of composite coconut shell carbon powder, a rich micropore, mesoporous and macropore structure is formed to improve adsorption performance. At the same time, modified silicone is used to combine with bisphenol A type epoxy resin to form a composite epoxy resin and melt and mix with TPU to form an adhesive material, and the bonding strength of the fabric is improved through hot press bonding technology.
It significantly improves the antibacterial and deodorizing properties of coconut shell activated carbon fabrics, and enhances its bonding strength and wrinkle resistance, ensuring a good retention rate of various properties after multiple washes.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabric processing, and in particular to a method for producing coconut shell activated carbon fabric. Background Art
[0002] With the rapid development of society and the continuous improvement of people's living standards, environmental and health issues have received increasing attention. Especially in the textile industry, the characteristics of single-layer fabrics are completely unable to meet people's living needs, so composite fabrics have emerged. Composite fabrics are made of textiles and other materials through coating or bonding; common composite fabrics include artificial leather, synthetic leather, rubber composite fabric, modified polyester composite fabric, foam plastic composite fabric, etc.
[0003] Coconut shell activated carbon is a material with high adsorption performance. It is made from coconut shells through a special process and can effectively adsorb harmful substances in the air, such as volatile organic compounds such as formaldehyde and benzene, as well as some odors and pigments. These characteristics of activated carbon have made it widely used in air purification, water treatment and other fields. However, applying the characteristics of activated carbon to textile fabrics to improve the environmental friendliness and health of fabrics is an area worth exploring.
[0004] When coconut shell activated carbon is used in composite fabrics in the prior art, the coconut shell activated carbon is usually mixed with hot melt adhesive through materials, and the coconut shell activated carbon is loaded on the composite fabric by the adhesion of the hot melt adhesive. However, the antibacterial and deodorizing properties of the coconut shell activated carbon itself are limited. When the coconut shell activated carbon fabric is used, its antibacterial and deodorizing properties need to be further improved. In addition, since the fabric is only bonded by adhesive, it is affected by the impurities on the surface of the fabric, the reaction activity of the surface of the fabric is low, the contact area between the fabric and the adhesive is limited, and the bonding strength of the fabric is poor.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a method for producing coconut shell activated carbon fabrics, which is used to solve the technical problems in the prior art that the antibacterial and deodorizing properties of coconut shell activated carbon fabrics need to be further improved and the bonding strength of the fabrics is poor.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A method for producing coconut shell activated carbon fabric comprises the following steps:
[0009] S1. Completely immerse the cotton and linen fiber fabric in a desizing solution at a temperature of 75-85°C for 40-50 minutes, and then post-treat to obtain a desizing fabric;
[0010] S2, adding bisphenol A epoxy resin, modified siloxane, and xylene into a reactor and stirring, raising the temperature of the reactor to reflux the system, adding catalyst and composite coconut shell carbon powder into the reactor in batches, and keeping the temperature to react until the acid value of the reaction system is lower than 3 mgKOH / g, and post-treating to obtain a composite epoxy resin;
[0011] S3, adding the composite epoxy resin, TPU and additives into a twin-screw extruder, and melt-extrude to obtain an adhesive material;
[0012] S4. Spread the desized fabric flat on a flat-plate press, raise the temperature of the flat-plate press to 130-150°C, evenly apply adhesive on the surface of the desized fabric to form an adhesive layer, cover the upper surface of the adhesive layer with another piece of desized fabric, keep hot pressing for 60-80s at a pressure of 0.3kPa, cool to room temperature, discharge, and obtain coconut shell activated carbon fabric.
[0013] Furthermore, in step S1, the desizing solution is composed of a desizing agent, hydrogen peroxide and alkali solution in a dosage ratio of 1g:2mL:70mL, the desizing agent is a commercially available cotton quick desizing agent with model number YH015, the content of hydrogen peroxide is 15-25%, and the alkali solution is a sodium hydroxide solution with a pH value of 9; the post-treatment operation includes: after the reaction is completed, washing the cotton and linen fiber fabric with purified water at a temperature of 40-45°C until the pH value of the cotton and linen fiber fabric is neutral, and drying naturally and ironing flat at a temperature of 25-35°C to obtain a desizing fabric.
[0014] Further, the composite coconut shell charcoal powder is processed by the following steps:
[0015] A1, activated coconut shell carbon powder, sodium citrate, sodium lauryl sulfate and deionized water were added to a reactor, ultrasonically dispersed for 60-80 minutes, stirred, and silver nitrate solution was added dropwise to the reactor at room temperature. After the addition was complete, the mixture was stirred at the temperature for 40-60 minutes, and the loaded coconut shell carbon powder was obtained by post-treatment;
[0016] The principle of the synthesis reaction includes: using sodium dodecyl sulfate as a dispersant to promote the dispersibility of activated coconut shell carbon powder and sodium citrate in an aqueous solution, so that silver nitrate reacts with sodium citrate to generate silver citrate, and the silver is uniformly loaded on the activated coconut shell carbon powder in the form of precipitation to form loaded coconut shell carbon powder.
[0017] A2, adding the loaded coconut shell carbon powder, anhydrous ethanol, KH-570 and sodium hydroxide solution into a reactor and stirring, raising the temperature of the reactor to 50-60°C, keeping the temperature for 4-5h, and post-treating to obtain modified coconut shell carbon powder;
[0018] The principle of the synthetic reaction includes: the siloxane bonds on KH-570 are hydrolyzed to form silanol groups, which then react with the active functional groups on the surface of the loaded coconut shell carbon powder to form chemical grafting modification.
[0019] A3. Add modified coconut shell carbon powder, 4-mercaptobutyric acid, catalyst and toluene into a reactor and stir. Raise the temperature of the reactor to reflux the system and keep the temperature for 4-6 hours. Post-treat to obtain composite coconut shell carbon powder.
[0020] The principle of the synthetic reaction is: the double bond of KH-570 modified on the modified coconut shell carbon powder undergoes a nucleophilic addition reaction with the thiol group on 4-mercaptobutyric acid under the action of a catalyst to prepare the loaded coconut shell carbon powder.
[0021] Further, in step A1, the amount ratio of the activated coconut shell carbon powder, sodium citrate, sodium dodecyl sulfate, deionized water and silver nitrate solution is 10g:5g:1g:100mL:12g, the silver nitrate solution is composed of silver nitrate and deionized water in an amount ratio of 1g:2mL, and the post-treatment operation includes: after the reaction is completed, suction filtration, washing the filter cake with deionized water 3 times and then washing it with anhydrous ethanol 2 times, and then transferring the filter cake to a drying oven at a temperature of 60-70°C, drying to constant weight, and obtaining the loaded coconut shell carbon powder; in step A2, the amount of the loaded coconut shell carbon powder, anhydrous ethanol, KH-570 and sodium hydroxide solution is The ratio of the modified coconut shell carbon powder, 4-mercaptobutyric acid, catalyst and toluene is 10g:4g:0.03g:100mL, and the catalyst is copper bromide. The post-treatment operation includes: after the reaction is completed, the temperature of the reactor is reduced to room temperature, suction filtration, and the filter cake is transferred to a drying oven at a temperature of 55-60°C, and dried to constant weight to obtain modified coconut shell carbon powder. In step A3, the amount ratio of the modified coconut shell carbon powder, 4-mercaptobutyric acid, catalyst and toluene is 10g:4g:0.03g:100mL, and the catalyst is copper bromide. The post-treatment operation includes: after the reaction is completed, the temperature of the reactor is reduced to room temperature, suction filtration, and the filter cake is transferred to a drying oven at a temperature of 60-70°C, and dried to constant weight to obtain composite coconut shell carbon powder.
[0022] Further, the activated coconut shell charcoal powder is processed by the following steps:
[0023] B1, use a crusher to crush coconut shell pieces, pass through a 10-20 mesh sieve to obtain coconut shell powder;
[0024] B2, placing the coconut shell powder in a tubular furnace, introducing a mixed gas into the tubular furnace, raising the temperature of the tubular furnace to 700-800°C, and heat preservation treatment for 2-3h, and the tubular furnace is naturally cooled to room temperature to obtain coconut shell charcoal powder;
[0025] B3, adding coconut shell carbon powder and potassium hydroxide solution into a reactor and stirring, raising the temperature of the reactor to 75-85° C., keeping the temperature for 90-120 min, and post-treating to obtain pre-treated coconut shell carbon powder;
[0026] B4. Place the coconut shell charcoal powder in a tubular furnace, introduce carbon dioxide into the tubular furnace, increase the temperature of the tubular furnace to 550-650°C at a heating rate of 2-5°C / min, keep the temperature for 2-3h, and post-treat to obtain activated coconut shell charcoal powder.
[0027] Furthermore, in step B2, the mixed gas is composed of nitrogen and carbon dioxide in a volume ratio of 2:1, and the gas flow rate of the mixed gas is 0.5-0.8L / min; in step B3, the amount ratio of the coconut shell carbon powder and the potassium hydroxide solution is 1g:8mL, the mass fraction of the potassium hydroxide solution is 25-45%, and the post-treatment operation includes: after the reaction is completed, filtering, draining off excess potassium hydroxide solution, and obtaining pre-treated coconut shell carbon powder with a humidity of 35-55%; in step B4, the gas flow rate of the carbon dioxide is 0.4-0.6L / min, and the post-treatment operation includes: after the reaction is completed, the tubular furnace is naturally cooled to room temperature, the carbon powder is taken out of the tubular furnace and washed to neutrality with purified water, the filter cake is transferred to a drying oven at a temperature of 70-80°C, dried to constant weight, and passed through a 80-1200 mesh sieve to obtain activated coconut shell carbon powder.
[0028] Furthermore, the preparation method of the modified siloxane is: add hexamethyl-1,15-dihydroxyoctasiloxane, epichlorohydrin, and a catalyst into a reactor and stir, increase the temperature of the reactor to reflux the system, keep the reaction warm for 4-6 hours, and post-treat to obtain the modified siloxane.
[0029] The principle of the synthesis reaction includes: under catalyst conditions, the hydroxyl group on hexamethyl-1,15-dihydroxyoctasiloxane undergoes a nucleophilic substitution reaction with the halogen on epichlorohydrin to form a modified siloxane of epoxy-terminated hexamethyloctasiloxane.
[0030] Furthermore, the dosage ratio of hexamethyl-1,15-dihydroxyoctasiloxane, epichlorohydrin and catalyst is 1g:8mL:0.05g, the catalyst is tetrabutylammonium bromide, and the post-treatment operation includes: after the reaction is completed, adding 20wt% sodium hydroxide solution to the reactor, stirring at a temperature of 4-6h, lowering the temperature of the reactor to room temperature, standing and separating the liquids, transferring the organic phase and washing it three times with a saturated sodium chloride solution, drying the organic phase with anhydrous magnesium sulfate for 2-3h, filtering, and transferring the filtrate to a rotary evaporator with a water bath temperature of 65-75°C, and removing the solvent under reduced pressure to obtain modified siloxane.
[0031] Further, in step S2, the amount ratio of the bisphenol A epoxy resin, modified siloxane, xylene, catalyst and composite coconut shell carbon powder is 10g:6g:80mL:0.1g:5g, the catalyst is tetrabutylammonium bromide, and the post-treatment operation includes: after the reaction is completed, the solvent is evaporated under reduced pressure to obtain a composite epoxy resin; in step S3, the weight ratio of the composite epoxy resin, TPU and additives is 10:7:0.2, and the additives are composed of a plasticizer, a curing agent, an anti-ultraviolet agent, and an antioxidant in a weight ratio of 5:2:1:2, the plasticizer is a phthalate, and the curing agent is cyclohexylamine, The invention discloses a method for preparing the invention of the present invention for preparing the invention of the present invention. The invention discloses a method for preparing the invention of the present invention for preparing the invention of the present invention for preparing the invention of the present invention for preparing the invention of the present invention for preparing the invention of the present invention for preparing the invention of the present invention for preparing the invention of the present invention for preparing the invention of the present invention for preparing the invention of the present invention for preparing the invention of the present invention for preparing the invention of the present invention for preparing the invention of the present invention for preparing the invention of the present invention for preparing the invention of the present invention for preparing the invention of the present invention for preparing the invention of the present invention for preparing the invention of the present invention for preparing the invention of the present invention for preparing the invention of the present invention for preparing the invention of the present invention for preparing the invention 2 .
[0032] The present invention has the following beneficial effects:
[0033] 1. The coconut shell activated carbon fabric of the present invention optimizes the processing technology of composite coconut shell carbon powder during the preparation process. In the carbonization process of coconut shell powder, mixed gas protection is adopted. The mixed gas can effectively control the carbonization rate and temperature distribution, thereby affecting the formation and expansion of pores in the carbon powder. Appropriate carbonization conditions can form rich micropores, mesopores and macropores, improve the adsorption performance of coconut shell carbon powder, and high-temperature treatment with potassium hydroxide can corrode the pores of the material and produce new micropores, thereby increasing the specific surface area of the carbon powder. High-temperature treatment under a carbon dioxide environment helps to remove residual impurities that may exist in the carbon powder, improve the purity of coconut shell carbon powder and the stability of the chemical structure, so that the activated coconut shell carbon powder can maintain good adsorption performance in different environments; after the activated coconut shell carbon powder is loaded with silver citrate, its surface is modified with KH-570 to form a carboxyl-modified modified coconut shell carbon powder. The carboxyl group is a strong polar functional group that can interact with the polar groups in the epoxy resin, thereby improving the dispersibility and compatibility of the coconut shell carbon powder in the epoxy resin, so that it can be evenly dispersed in the epoxy resin, and the silver citrate loaded on the composite coconut shell carbon powder gives the coconut shell carbon powder good antibacterial properties.
[0034] 2. The coconut shell activated carbon fabric of the present invention, during the preparation process, uses modified siloxane and bisphenol A epoxy resin as raw materials, and uses composite coconut shell carbon powder as a blocking cross-linking agent to form a composite epoxy resin copolymerized with modified siloxane and bisphenol A epoxy resin with composite coconut shell carbon powder as a cross-linking agent, and melt-mixes the composite epoxy resin with TPU to form an adhesive; the coconut shell carbon powder itself has certain antibacterial properties, and after the coconut shell carbon powder is loaded with silver citrate, its antibacterial effect is further enhanced, and the coconut shell carbon powder, as a blocking cross-linking agent, is uniformly dispersed in the adhesive in the form of chemical bonding, The problem of coconut shell activated carbon powder migration and loss during the use of coconut shell activated carbon fabrics is avoided, thereby achieving long-lasting deodorizing and antibacterial effects. The silicone material has excellent flexibility and can effectively relieve stress and reduce deformation when subjected to external forces. Bisphenol A epoxy resin has high mechanical strength and rigidity, which helps to enhance the overall structural stability of the composite epoxy resin. TPU is a material with excellent elasticity and resilience. By increasing the degree of cross-linking of modified silicone and bisphenol A epoxy resin and optimizing the weight ratio of composite epoxy resin to TPU, the wrinkle resistance of the fabric is improved.
[0035] 3. In the preparation process of the coconut shell activated carbon fabric of the present invention, the cotton and linen fiber fabric is desized by a desizing solution to remove pectin, grease, wax and other impurities on the cotton and linen fiber fabric, and the cotton and linen fiber fabric is activated to improve the surface activity of the cotton and linen fiber fabric. The composite epoxy resin formed by copolymerization of modified siloxane and bisphenol A epoxy resin has high adhesion and mechanical strength, and cooperates with TPU to improve the bonding performance of the adhesive. The fibers of the cotton and linen fiber fabric after desizing are more exposed and clean, and have good reaction activity, which is conducive to the penetration of the adhesive into the cotton and linen fiber fabric. While increasing the contact area between the fibers, it can also chemically cross-link with the adhesive, so that the adhesive and the fiber form a strong bond, thereby enhancing the adhesion between the adhesive and the fabric and the overall peeling strength of the fabric. The copolymer structure of siloxane and bisphenol A epoxy resin in the composite epoxy resin gives the adhesive good flexibility and strength, while the addition of TPU further enhances the elasticity and resilience of the adhesive. The composite coconut shell carbon powder, as a capping cross-linking agent, plays a role in enhancing the internal cross-linking density in the adhesive, which helps to improve the cohesion and stability of the adhesive, thereby further enhancing the peeling strength between the adhesive and the cotton and linen fiber fabric. DETAILED DESCRIPTION
[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Among the materials used in the present invention, the desizing agent is a cotton quick desizing agent produced by Jiangsu Yahui Textile Technology Co., Ltd., model YH015; the TPU is a product of Yantai Meirui, specification E395A; the domestic model of bisphenol A epoxy resin is E-42.
[0038] Example 1
[0039] This embodiment provides a method for preparing composite coconut shell carbon powder for coconut shell activated carbon fabric, comprising the following steps:
[0040] S1. Preparation of coconut shell charcoal powder
[0041] Use a crusher to crush the coconut shell flakes and pass them through a 10-mesh sieve to obtain coconut shell powder;
[0042] The coconut shell powder was placed in a tubular furnace, and a mixed gas consisting of nitrogen and carbon dioxide in a volume ratio of 2:1 was introduced into the tubular furnace at a gas flow rate of 0.5 L / min. The temperature of the tubular furnace was increased to 700°C and kept warm for 2 hours. The tubular furnace was naturally cooled to room temperature to obtain coconut shell charcoal powder.
[0043] S2. Preparation of activated coconut shell charcoal powder
[0044] Weigh: 50g of coconut shell carbon powder and 400mL of 25wt% potassium hydroxide solution are added into a reactor and stirred. The temperature of the reactor is raised to 75°C and kept warm for 90min. After the reaction is completed, filter and drain the excess potassium hydroxide solution to obtain pre-treated coconut shell carbon powder with a humidity of 35%;
[0045] The coconut shell carbon powder was placed in a tubular furnace, and carbon dioxide was introduced into the tubular furnace at a gas flow rate of 0.4 L / min. The temperature of the tubular furnace was increased to 550°C at a heating rate of 2°C / min. The tube furnace was kept warm for 2 hours. The tube furnace was naturally cooled to room temperature. The carbon powder was taken out of the tube furnace and washed with purified water until it was neutral. The filter cake was transferred to a drying oven at a temperature of 70°C, dried to constant weight, and passed through an 80-mesh sieve to obtain activated coconut shell carbon powder.
[0046] S3. Preparation of loaded coconut shell carbon powder
[0047] Mix silver nitrate and deionized water in a ratio of 1 g:2 mL to obtain a silver nitrate solution for later use;
[0048] Weigh: 200 g of activated coconut shell carbon powder, 100 g of sodium citrate, 20 g of sodium dodecyl sulfate and 2000 mL of deionized water, add them into a reactor, ultrasonically disperse for 60 min, stir, and add 240 g of silver nitrate solution to the reactor at room temperature. After the addition is complete, keep warm and stir for 40 min. After the reaction is completed, filter, wash the filter cake with deionized water 3 times and then with anhydrous ethanol 2 times, then transfer the filter cake to a drying oven at 60 ° C, dry to constant weight, and obtain loaded coconut shell carbon powder.
[0049] S4. Preparation of modified coconut shell charcoal powder
[0050] Weigh: 200 g of loaded coconut shell carbon powder, 1600 mL of anhydrous ethanol, 120 g of KH-570 and 400 mL of 15 wt% sodium hydroxide solution, add into the reactor and stir, raise the temperature of the reactor to 50 ° C, keep warm and react for 4 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, transfer the filter cake to a drying oven at a temperature of 55 ° C, and dry to constant weight to obtain modified coconut shell carbon powder.
[0051] S5. Preparation of composite coconut shell carbon powder
[0052] Weigh: 200 g of modified coconut shell charcoal powder, 80 g of 4-mercaptobutyric acid, 0.6 g of copper bromide and 2000 mL of toluene, add into the reactor and stir, raise the temperature of the reactor to the reflux of the system, keep warm and react for 4 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, transfer the filter cake to a drying oven at a temperature of 60°C, and dry to constant weight to obtain composite coconut shell charcoal powder.
[0053] Example 2
[0054] This embodiment provides a method for preparing composite coconut shell carbon powder for coconut shell activated carbon fabric, comprising the following steps:
[0055] S1. Preparation of coconut shell charcoal powder
[0056] Use a crusher to crush the coconut shell flakes and pass them through a 15-mesh sieve to obtain coconut shell powder;
[0057] The coconut shell powder was placed in a tubular furnace, and a mixed gas consisting of nitrogen and carbon dioxide in a volume ratio of 2:1 was introduced into the tubular furnace at a gas flow rate of 0.7 L / min. The temperature of the tubular furnace was increased to 750°C and kept warm for 2.5 hours. The tubular furnace was naturally cooled to room temperature to obtain coconut shell charcoal powder.
[0058] S2. Preparation of activated coconut shell charcoal powder
[0059] Weigh: 50g of coconut shell carbon powder and 400mL of 35wt% potassium hydroxide solution are added into a reactor and stirred. The temperature of the reactor is raised to 80°C and kept warm for 105min. After the reaction is completed, filter and drain the excess potassium hydroxide solution to obtain pre-treated coconut shell carbon powder with a humidity of 45%.
[0060] The coconut shell carbon powder was placed in a tubular furnace, and carbon dioxide was introduced into the tubular furnace at a gas flow rate of 0.5 L / min. The temperature of the tubular furnace was increased to 600°C at a heating rate of 3°C / min. The temperature was kept warm for 2.5 hours. The tubular furnace was naturally cooled to room temperature. The carbon powder was taken out of the tubular furnace and washed with purified water until it was neutral. The filter cake was transferred to a drying oven at a temperature of 75°C, dried to constant weight, and passed through an 800-mesh sieve to obtain activated coconut shell carbon powder.
[0061] S3. Preparation of loaded coconut shell carbon powder
[0062] Mix silver nitrate and deionized water in a ratio of 1 g:2 mL to obtain a silver nitrate solution for later use;
[0063] Weigh: 200 g of activated coconut shell carbon powder, 100 g of sodium citrate, 20 g of sodium dodecyl sulfate and 2000 mL of deionized water, add them into a reactor, ultrasonically disperse for 70 min, stir, and add 240 g of silver nitrate solution to the reactor at room temperature. After the addition is complete, keep warm and stir for 50 min. After the reaction is completed, filter, wash the filter cake with deionized water 3 times and then with anhydrous ethanol 2 times, then transfer the filter cake to a drying oven at 65 ° C, dry to constant weight, and obtain loaded coconut shell carbon powder.
[0064] S4. Preparation of modified coconut shell carbon powder
[0065] Weigh: 200 g of loaded coconut shell carbon powder, 1600 mL of anhydrous ethanol, 120 g of KH-570 and 400 mL of 20 wt% sodium hydroxide solution, add into the reactor and stir, raise the temperature of the reactor to 55 ° C, keep warm and react for 4.5 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, transfer the filter cake to a drying oven at a temperature of 57 ° C, and dry to constant weight to obtain modified coconut shell carbon powder.
[0066] S5. Preparation of composite coconut shell carbon powder
[0067] Weigh: 200 g of modified coconut shell carbon powder, 80 g of 4-mercaptobutyric acid, 0.6 g of copper bromide and 2000 mL of toluene, add into the reactor and stir, raise the temperature of the reactor to the reflux of the system, and keep the reaction for 5 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, transfer the filter cake to a drying oven at a temperature of 65°C, and dry to constant weight to obtain composite coconut shell carbon powder.
[0068] Example 3
[0069] This embodiment provides a method for preparing composite coconut shell carbon powder for coconut shell activated carbon fabric, comprising the following steps:
[0070] S1. Preparation of coconut shell charcoal powder
[0071] Use a crusher to crush the coconut shell flakes and pass them through a 20-mesh sieve to obtain coconut shell powder;
[0072] The coconut shell powder was placed in a tubular furnace, and a mixed gas consisting of nitrogen and carbon dioxide in a volume ratio of 2:1 was introduced into the tubular furnace at a gas flow rate of 0.8 L / min. The temperature of the tubular furnace was increased to 800°C and kept warm for 3 hours. The tubular furnace was naturally cooled to room temperature to obtain coconut shell charcoal powder.
[0073] S2. Preparation of activated coconut shell charcoal powder
[0074] Weigh: 50g of coconut shell carbon powder and 400mL of 45wt% potassium hydroxide solution are added into a reactor and stirred. The temperature of the reactor is raised to 85°C and kept warm for 120min. After the reaction is completed, filter and drain the excess potassium hydroxide solution to obtain pre-treated coconut shell carbon powder with a humidity of 55%.
[0075] The coconut shell carbon powder was placed in a tubular furnace, and carbon dioxide was introduced into the tubular furnace at a gas flow rate of 0.6 L / min. The temperature of the tubular furnace was increased to 650°C at a heating rate of 5°C / min. The tube furnace was kept warm for 3 hours. The tube furnace was naturally cooled to room temperature. The carbon powder was taken out of the tube furnace and washed with purified water until it was neutral. The filter cake was transferred to a drying oven at 80°C, dried to constant weight, and passed through a 1200-mesh sieve to obtain activated coconut shell carbon powder.
[0076] S3. Preparation of loaded coconut shell carbon powder
[0077] Mix silver nitrate and deionized water in a ratio of 1 g:2 mL to obtain a silver nitrate solution for later use;
[0078] Weigh: 200 g of activated coconut shell carbon powder, 100 g of sodium citrate, 20 g of sodium dodecyl sulfate and 2000 mL of deionized water, add them into a reactor, ultrasonically disperse for 80 min, stir, and add 240 g of silver nitrate solution to the reactor at room temperature. After the addition is complete, keep warm and stir for 60 min. After the reaction is completed, filter, wash the filter cake with deionized water 3 times and then with anhydrous ethanol 2 times, then transfer the filter cake to a drying oven at 70°C, dry to constant weight, and obtain loaded coconut shell carbon powder.
[0079] S4. Preparation of modified coconut shell carbon powder
[0080] Weigh: 200 g of loaded coconut shell carbon powder, 1600 mL of anhydrous ethanol, 120 g of KH-570 and 400 mL of 25 wt% sodium hydroxide solution, add into the reactor and stir, raise the temperature of the reactor to 60 ° C, keep warm and react for 5 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, transfer the filter cake to a drying oven at a temperature of 60 ° C, and dry to constant weight to obtain modified coconut shell carbon powder.
[0081] S5. Preparation of composite coconut shell carbon powder
[0082] Weigh: 200 g of modified coconut shell charcoal powder, 80 g of 4-mercaptobutyric acid, 0.6 g of copper bromide and 2000 mL of toluene, add into the reactor and stir, raise the temperature of the reactor to the reflux of the system, keep warm and react for 6 hours, after the reaction is completed, lower the temperature of the reactor to room temperature, filter, transfer the filter cake to a drying oven at a temperature of 70°C, dry to constant weight, and obtain composite coconut shell charcoal powder.
[0083] Example 4
[0084] This embodiment provides a method for producing coconut shell activated carbon fabric, comprising the following steps:
[0085] Step 1: Prepare desizing fabric
[0086] The desizing agent, 15 wt% hydrogen peroxide and sodium hydroxide solution with a pH of 9 were mixed uniformly in a dosage ratio of 1 g: 2 mL: 70 mL to obtain a desizing solution for later use;
[0087] Completely immerse the cotton and linen fiber fabric in a desizing solution at a temperature of 75°C for 40 minutes. After the reaction is completed, wash the cotton and linen fiber fabric with purified water at a temperature of 40°C until the pH of the cotton and linen fiber fabric is neutral. Dry it naturally at a temperature of 25°C, and iron it flat to obtain the desizing fabric.
[0088] Step 2: Preparation of composite epoxy resin
[0089] Weigh: 50 g of hexamethyl-1,15-dihydroxyoctasiloxane, 400 mL of epichlorohydrin, and 0.25 g of tetrabutylammonium bromide, add them to a reactor and stir, raise the temperature of the reactor to reflux the system, and keep the temperature for 4 hours. After the reaction is completed, add 20 wt% sodium hydroxide solution to the reactor, keep the temperature and stir for 4 hours, lower the temperature of the reactor to room temperature, stand and separate the liquids, transfer the organic phase and wash it three times with a saturated sodium chloride solution, dry the organic phase with anhydrous magnesium sulfate for 2 hours, filter, transfer the filtrate to a rotary evaporator with a water bath temperature of 65°C, and evaporate the solvent under reduced pressure to obtain modified siloxane;
[0090] Weigh: 100 g of bisphenol A epoxy resin, 60 g of modified siloxane, and 800 mL of xylene are added to a reactor and stirred. The temperature of the reactor is raised to reflux, and 1 g of tetrabutylammonium bromide and 50 g of the composite coconut shell carbon powder prepared in Example 1 are added to the reactor in batches. The reaction is kept warm until the acid value of the reaction system reaches 3 mgKOH / g. After the reaction is completed, the solvent is evaporated under reduced pressure to obtain a composite epoxy resin.
[0091] Step 3: Prepare adhesive
[0092] Di(2-ethylhexyl)phthalate, cyclohexylamine, ultraviolet absorber UV-0, and tea polyphenols are uniformly mixed in a weight ratio of 5:2:1:2 to obtain an additive for later use;
[0093] Weigh: 1000 g of composite epoxy resin, 700 g of TPU and 20 g of additives are added to a twin-screw extruder, the temperatures of the eight temperature sections of the twin-screw extruder from the feed end to the discharge port are 175° C., 175° C., 185° C., 190° C., 190° C., 190° C., 190° C., 195° C., the main shaft speed of the twin-screw extruder is 15 r / min, and the adhesive is melt-extruded through the twin-screw extruder to obtain.
[0094] Step 4: Preparation of coconut shell activated carbon fabric
[0095] Lay the desizing fabric flat on a flat-plate pressing machine, raise the temperature of the flat-plate pressing machine to 130°C, and heat it at 10g / m 2 The adhesive is evenly coated on the surface of the desized fabric with a coating amount of to form an adhesive layer on the surface of the desized fabric, and then another piece of desized fabric is covered on the upper surface of the adhesive layer. Under a pressure of 0.3 kPa, the adhesive is kept hot-pressed for 60 seconds, cooled to room temperature, and discharged to obtain coconut shell activated carbon fabric.
[0096] Example 5
[0097] This embodiment provides a method for producing coconut shell activated carbon fabric, comprising the following steps:
[0098] Step 1: Prepare desizing fabric
[0099] The desizing agent, 20 wt% hydrogen peroxide and sodium hydroxide solution with a pH of 9 were mixed uniformly in a dosage ratio of 1 g: 2 mL: 70 mL to obtain a desizing solution for later use;
[0100] Completely immerse the cotton and linen fiber fabric in a desizing solution at a temperature of 80°C for 45 minutes. After the reaction is completed, wash the cotton and linen fiber fabric with purified water at a temperature of 43°C until the pH of the cotton and linen fiber fabric is neutral. Dry it naturally at a temperature of 30°C and iron it flat to obtain the desizing fabric.
[0101] Step 2: Preparation of composite epoxy resin
[0102] Weigh: 50 g of hexamethyl-1,15-dihydroxyoctasiloxane, 400 mL of epichlorohydrin, and 0.25 g of tetrabutylammonium bromide, add them to a reactor and stir, raise the temperature of the reactor to reflux the system, and keep the temperature for reaction for 5 hours. After the reaction is completed, add 20 wt% sodium hydroxide solution to the reactor, keep the temperature and stir for 5 hours, lower the temperature of the reactor to room temperature, stand and separate the liquids, transfer the organic phase and wash it three times with a saturated sodium chloride solution, dry the organic phase with anhydrous magnesium sulfate for 2.5 hours, filter, transfer the filtrate to a rotary evaporator with a water bath temperature of 70°C, and evaporate the solvent under reduced pressure to obtain modified siloxane;
[0103] Weigh: 100 g of bisphenol A epoxy resin, 60 g of modified siloxane, and 800 mL of xylene are added to a reactor and stirred. The temperature of the reactor is raised to reflux. 1 g of tetrabutylammonium bromide and 50 g of the composite coconut shell carbon powder prepared in Example 2 are added to the reactor in batches. The reaction is kept warm until the acid value of the reaction system reaches 2.5 mgKOH / g. After the reaction is completed, the solvent is evaporated under reduced pressure to obtain a composite epoxy resin.
[0104] Step 3: Prepare adhesive
[0105] Dimethyl phthalate, acrylamine, ultraviolet absorber UV-9, and butylated hydroxyanisole are uniformly mixed in a weight ratio of 5:2:1:2 to obtain an additive for later use;
[0106] Weigh: 1000 g of composite epoxy resin, 700 g of TPU and 20 g of additives are added to a twin-screw extruder, the temperatures of the eight temperature sections of the twin-screw extruder from the feed end to the discharge port are 175° C., 175° C., 185° C., 190° C., 190° C., 190° C., 190° C., 195° C., the main shaft speed of the twin-screw extruder is 15 r / min, and the adhesive is melt-extruded through the twin-screw extruder to obtain.
[0107] Step 4: Preparation of coconut shell activated carbon fabric
[0108] Lay the desizing fabric flat on a flat-plate pressing machine, raise the temperature of the flat-plate pressing machine to 140°C, and heat it at 12g / m 2 The adhesive is evenly coated on the surface of the desized fabric with a coating amount of to form an adhesive layer on the surface of the desized fabric, and then another piece of desized fabric is covered on the upper surface of the adhesive layer. Under a pressure of 0.3 kPa, the mixture is kept hot-pressed for 70 seconds, cooled to room temperature, and discharged to obtain coconut shell activated carbon fabric.
[0109] Example 6
[0110] This embodiment provides a method for producing coconut shell activated carbon fabric, comprising the following steps:
[0111] Step 1: Prepare desizing fabric
[0112] The desizing agent, 25 wt% hydrogen peroxide and sodium hydroxide solution with a pH of 9 were mixed uniformly in a dosage ratio of 1 g: 2 mL: 70 mL to obtain a desizing solution for later use;
[0113] Completely immerse the cotton and linen fiber fabric in a desizing solution at a temperature of 85°C for 50 minutes. After the reaction is completed, wash the cotton and linen fiber fabric with purified water at a temperature of 45°C until the pH of the cotton and linen fiber fabric is neutral. Dry it naturally at a temperature of 35°C, and iron it flat to obtain the desizing fabric.
[0114] Step 2: Preparation of composite epoxy resin
[0115] Weigh: 50 g of hexamethyl-1,15-dihydroxyoctasiloxane, 400 mL of epichlorohydrin, and 0.25 g of tetrabutylammonium bromide, add them to a reactor and stir, raise the temperature of the reactor to reflux the system, and keep the temperature for 6 hours. After the reaction is completed, add 20 wt% sodium hydroxide solution to the reactor, keep the temperature and stir for 6 hours, lower the temperature of the reactor to room temperature, stand and separate the liquids, transfer the organic phase and wash it three times with a saturated sodium chloride solution, dry the organic phase with anhydrous magnesium sulfate for 3 hours, filter, transfer the filtrate to a rotary evaporator with a water bath temperature of 75°C, and evaporate the solvent under reduced pressure to obtain modified siloxane;
[0116] Weigh: 100 g of bisphenol A epoxy resin, 60 g of modified siloxane, and 800 mL of xylene are added to a reactor and stirred. The temperature of the reactor is raised to reflux, and 1 g of tetrabutylammonium bromide and 50 g of the composite coconut shell carbon powder prepared in Example 3 are added to the reactor in batches. The reaction is kept warm until the acid value of the reaction system reaches 2 mgKOH / g. After the reaction is completed, the solvent is evaporated under reduced pressure to obtain a composite epoxy resin.
[0117] Step 3: Prepare adhesive
[0118] Di(2-ethylhexyl)phthalate, cyclohexylamine, ultraviolet absorber UV-531, and butylated hydroxytoluene are uniformly mixed in a weight ratio of 5:2:1:2 to obtain an additive for later use;
[0119] Weigh: 1000 g of composite epoxy resin, 700 g of TPU and 20 g of additives are added to a twin-screw extruder, the temperatures of the eight temperature sections of the twin-screw extruder from the feed end to the discharge port are 175° C., 175° C., 185° C., 190° C., 190° C., 190° C., 190° C., 195° C., the main shaft speed of the twin-screw extruder is 15 r / min, and the adhesive is melt-extruded through the twin-screw extruder to obtain.
[0120] Step 4: Preparation of coconut shell activated carbon fabric
[0121] Lay the desizing fabric flat on a flat-plate press, raise the temperature of the flat-plate press to 150°C, and heat it at 14g / m 2 The adhesive is evenly coated on the surface of the desized fabric with a coating amount of to form an adhesive layer on the surface of the desized fabric, and then another piece of desized fabric is covered on the upper surface of the adhesive layer. Under a pressure of 0.3 kPa, the adhesive is kept hot-pressed for 80 seconds, cooled to room temperature, and discharged to obtain coconut shell activated carbon fabric.
[0122] Comparative Example 1
[0123] The difference between this comparative example and Example 6 is that step one is eliminated, and the desizing fabric in step five is replaced by the cotton and linen fiber fabric in step one.
[0124] Comparative Example 2
[0125] The difference between this comparative example and Example 6 is that, in the process of preparing the composite epoxy resin in step 2, no modified siloxane is added.
[0126] Comparative Example 3
[0127] The difference between this comparative example and Example 6 is that, in the process of preparing the adhesive in step 3, no TPU is added.
[0128] Comparative Example 4
[0129] The difference between this comparative example and Example 6 is that, when preparing the composite coconut shell carbon powder in step 2, step S4-5 is omitted, and the composite coconut shell carbon powder is replaced by the loaded coconut shell carbon powder in step S3.
[0130] Comparative Example 5
[0131] The difference between this comparative example and Example 6 is that, when preparing the composite coconut shell carbon powder in step 2, step S3 is omitted, and the activated coconut shell carbon powder in step S2 is used instead of the loaded coconut shell carbon powder in step S4 for reaction.
[0132] Comparative Example 6
[0133] The difference between this comparative example and Example 6 is that, when preparing the composite coconut shell carbon powder in step 2, step S2 is omitted, and the coconut shell carbon powder in step S1 is used to replace the activated coconut shell carbon powder in step S2 for reaction.
[0134] Performance Test:
[0135] The deodorization performance, antibacterial performance, bonding strength and wrinkle resistance of the coconut shell activated carbon fabrics prepared in Examples 4-6 and Comparative Examples 1-6 were tested. The deodorization performance was measured by referring to the standard GB / T 33610.1-2019 "Determination of Deodorization Performance of Textiles Part 1: General Rules" to determine the reduction rate of the concentration of odor chemical components of the sample; the antibacterial performance was measured by referring to the standard GB / T20944.2-2007 "Evaluation of Antibacterial Performance of Textiles Part 2: Absorption Method" to determine the antibacterial rate of the sample against Staphylococcus aureus, Klebsiella pneumoniae and Escherichia coli; the bonding strength was measured by referring to the standard FZ / T 72016-2012 "Knitted Composite Clothing Fabrics" to determine the peeling strength of the sample; the wrinkle resistance was rated by referring to the standard: GB / T 29257-2012 "Appearance Method for Evaluation of Wrinkle Recovery of Textile Fabrics" to rate the appearance wrinkling degree of the sample; the specific test results are shown in the following table:
[0136]
[0137] Data Analysis:
[0138] Comparative analysis of the data in the above table shows that the coconut shell activated carbon fabric prepared by the present invention has a concentration reduction rate of 92.5% for odorous chemical components, a peeling strength of 76.0N, a wrinkle degree of 5, an antibacterial rate of 87% for Staphylococcus aureus, an antibacterial rate of 85.3% for Klebsiella pneumoniae, and an antibacterial rate of 88.6% for Escherichia coli. All test data are better than those of the comparative example, and after 100 After the first cycle of washing, the retention rates of various properties of the coconut shell activated carbon fabric are all higher than 85%, indicating that the present invention processes the coconut shell carbon powder, compounds it with modified siloxane and bisphenol A epoxy resin to prepare a composite epoxy resin, and then compounds the composite epoxy resin with TPU to prepare an adhesive material, which is then bonded to the cotton and linen fiber fabric. This not only effectively improves the deodorizing and antibacterial properties of the coconut shell activated carbon, but also improves its bonding strength and anti-wrinkle properties. Moreover, after multiple washings, the retention rates of various performance parameters are good.
[0139] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0140] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0141] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for producing coconut shell activated carbon fabric, characterized in that: The following steps are involved: S1. Completely immerse the cotton and linen fiber fabric in a desizing solution at a temperature of 75-85° C. for 40-50 minutes, and perform post-treatment to obtain a desizing fabric, wherein the desizing solution is composed of a desizing agent, hydrogen peroxide, and alkali solution in a dosage ratio of 1 g: 2 mL: 70 mL; S2, adding bisphenol A epoxy resin, modified siloxane, and xylene into a reactor and stirring, raising the temperature of the reactor to reflux the system, adding catalyst and composite coconut shell carbon powder into the reactor in batches, and keeping the temperature to react until the acid value of the reaction system is lower than 3 mgKOH / g, and post-treating to obtain a composite epoxy resin; S3, adding the composite epoxy resin, TPU and additives into a twin-screw extruder, and melt-extrude to obtain an adhesive material; S4, laying the desizing fabric on a flat-plate pressing machine, raising the temperature of the flat-plate pressing machine to 130-150°C, evenly coating the surface of the desizing fabric with adhesive to form an adhesive layer, covering the upper surface of the adhesive layer with another piece of desizing fabric, keeping the heat and hot pressing for 60-80s at a pressure of 0.3kPa, cooling to room temperature, discharging, and obtaining coconut shell activated carbon fabric; Composite coconut shell charcoal powder is processed by the following steps: A1, activated coconut shell carbon powder, sodium citrate, sodium lauryl sulfate and deionized water were added to a reactor, ultrasonically dispersed for 60-80 minutes, stirred, and silver nitrate solution was added dropwise to the reactor at room temperature. After the addition was complete, the mixture was stirred at the temperature for 40-60 minutes, and the loaded coconut shell carbon powder was obtained by post-treatment; A2, adding the loaded coconut shell carbon powder, anhydrous ethanol, KH-570 and sodium hydroxide solution into a reactor and stirring, raising the temperature of the reactor to 50-60°C, keeping the temperature for 4-5h, and post-treating to obtain modified coconut shell carbon powder; A3, adding modified coconut shell carbon powder, 4-mercaptobutyric acid, catalyst and toluene into a reactor and stirring, raising the temperature of the reactor to reflux the system, keeping the temperature for 4-6 hours, and post-treating to obtain composite coconut shell carbon powder; Activated coconut shell charcoal powder is processed by the following steps: B1, use a crusher to crush coconut shell pieces, pass through a 10-20 mesh sieve to obtain coconut shell powder; B2, placing the coconut shell powder in a tubular furnace, introducing a mixed gas into the tubular furnace, raising the temperature of the tubular furnace to 700-800°C, and heat preservation treatment for 2-3h, and the tubular furnace is naturally cooled to room temperature to obtain coconut shell charcoal powder; B3, adding coconut shell carbon powder and potassium hydroxide solution into a reactor and stirring, raising the temperature of the reactor to 75-85° C., keeping the temperature for 90-120 min, and post-treating to obtain pre-treated coconut shell carbon powder; B4. Place the coconut shell charcoal powder in a tubular furnace, introduce carbon dioxide into the tubular furnace, increase the temperature of the tubular furnace to 550-650°C at a heating rate of 2-5°C / min, keep the temperature for 2-3h, and post-treat to obtain activated coconut shell charcoal powder.
2. The method for producing coconut shell activated carbon fabric according to claim 1, characterized in that: In step S1, the desizing agent is a commercially available cotton rapid desizing agent, model number YH015, the content of the hydrogen peroxide is 15-25wt%, and the alkali solution is a sodium hydroxide solution with a pH value of 9.
3. The method for producing coconut shell activated carbon fabric according to claim 1, characterized in that: In step A1, the amount ratio of the activated coconut shell carbon powder, sodium citrate, sodium dodecyl sulfate, deionized water and silver nitrate solution is 10g:5g:1g:100mL:12g, and the silver nitrate solution is composed of silver nitrate and deionized water in an amount ratio of 1g:2mL; in step A2, the amount ratio of the loaded coconut shell carbon powder, anhydrous ethanol, KH-570 and sodium hydroxide solution is 10g:80mL:6g:20mL; in step A3, the amount ratio of the modified coconut shell carbon powder, 4-mercaptobutyric acid, catalyst and toluene is 10g:4g:0.03g:100mL, and the catalyst is copper bromide.
4. The method for producing coconut shell activated carbon fabric according to claim 1, characterized in that: In step B2, the mixed gas is composed of nitrogen and carbon dioxide in a volume ratio of 2:1, and the gas flow rate of the mixed gas is 0.5-0.8 L / min; in step B3, the amount ratio of the coconut shell charcoal powder and the potassium hydroxide solution is 1g:8mL, and the mass fraction of the potassium hydroxide solution is 25-45%; in step B4, the gas flow rate of the carbon dioxide is 0.4-0.6 L / min.
5. The method for producing coconut shell activated carbon fabric according to claim 1, characterized in that: The preparation method of modified siloxane is as follows: hexamethyl-1,15-dihydroxyoctasiloxane, epichlorohydrin and a catalyst are added into a reaction kettle and stirred, the temperature of the reaction kettle is increased to reflux the system, the reaction is kept warm for 4-6 hours, and the modified siloxane is obtained by post-treatment.
6. The method for producing coconut shell activated carbon fabric according to claim 5, characterized in that: The dosage ratio of hexadecyl-1,15-dihydroxyoctasiloxane, epichlorohydrin and catalyst is 1g:8mL: 0.05g, the catalyst is tetrabutylammonium bromide, and the post-treatment operation includes: after the reaction is completed, adding 20wt% sodium hydroxide solution to the reactor, stirring at the temperature for 4-6h, lowering the temperature of the reactor to room temperature, standing and separating the liquids, transferring the organic phase and washing it three times with a saturated sodium chloride solution, drying the organic phase with anhydrous magnesium sulfate for 2-3h, filtering, transferring the filtrate to a rotary evaporator with a water bath temperature of 65-75°C, and removing the solvent under reduced pressure to obtain modified siloxane.
7. The method for producing coconut shell activated carbon fabric according to claim 1, characterized in that: In step S2, the amount ratio of the bisphenol A epoxy resin, modified siloxane, xylene, catalyst and composite coconut shell carbon powder is 10g:6g:80mL:0.1g:5g, and the catalyst is tetrabutylammonium bromide; in step S3, the weight ratio of the composite epoxy resin, TPU and additives is 10:7:0.2, and the additives are composed of plasticizer, curing agent, anti-ultraviolet agent and antioxidant in a weight ratio of 5:2:1:
2. The temperatures of the eight temperature sections of the twin-screw extruder from the feed end to the discharge port are 175°C, 175°C, 185°C, 190°C, 190°C, 190°C, 190°C, 195°C, and the spindle speed of the twin-screw extruder is 15r / min; in step S4, the coating amount of the adhesive is 10-14g / m 2 .
Citation Information
Patent Citations
Preparation method and use of carbon molecular sieve
CN101935032A
Nanometer silver-loaded active carbon and preparation method thereof
CN103232035A
Processing method of textile fabric for preventing electromagnetic radiation
CN109795192A
Medical ultrathin TPU film and preparation method thereof
CN112457656A